Maqashid Sharia Analysis on Personal Data Protection from the Dangers of Artificial Intelligence Misuse - Farid, Achmad Miftah; Pratama, Fauzan Arya; Sulistyowati, Dewi (Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the use of AI from the perspective of prophetic law, with an emphasis on the values of justice, benefit, and equality of rights in Islamic law, based on maqashid sharia, with the intention of protecting personal data from the uncontrolled use of AI. Additionally, it highlights the role of community organizations, particularly Muhammadiyah, in providing education and advocacy related to the protection of personal data in accordance with progressive Islamic values. The socio-legal method enabled a comprehensive analysis of the social impact and legal regulations on the protection of personal data in the context of the rapid development of AI. The results of the analysis of legal facts and empirical information show that the uncontrolled use of AI is detrimental to society. The misuse of AI has been linked to several personal data leakage issues in various countries. The integration of Islamic values, based on maqashid sharia, into data protection policies is crucial for preventing the unethical exploitation of technology and ensuring that innovation remains within the benefit of the ummah. Personal data protection is intended to maintain digital ethics based on hifzun-nafs (protection of life), hifdzul-‘aql (protection of reason), and hifdzul-‘ird (protection of honor), which can provide moral and ethical justification for the development of more humanized personal data regulations in the AI era.